Critically Ill Patients: Family Experiences of Interfacility Transfers From Rural to Urban Centers and Impact on Family Relationships. (February 2023) - Burns, Margie; Bally, Jill; Burles, Meridith; Peacock, Shelley
A critical illness event is intensely stressful for family members and can lead to negative psychological, emotional, social and financial consequences. In geographically rural areas, critically ill patients may require an interfacility transfer to an urban centre for advanced critical care services. In this context, research suggests that these family members from rural areas experience additional burdens, yet little is known about these experiences. An interpretive phenomenological approach was used to explore lived experiences of family members from rural areas whose critically ill relative undergoes an interfacility transfer to an urban centre for advanced critical care services. Participants described feelings of vulnerability in the urban centre, the need to protect the critically ill patient and other relatives, maintaining responsibilities at home, navigating family relationships, and a loss of connection during the transfer window. These findings may better position nurses to address family members' stress and anxiety during this experience.